New blocking antibodies impede adhesion, migration and survival of ovarian cancer cells, highlighting MFGE8 as a potential therapeutic target of human ovarian carcinoma. - Lorenzo Tibaldi; Shirley Leyman; André Nicolas; Sofie Notebaert; Melissa Dewulf; Thu Hoa Ngo; Claudia Zuany-Amorim; Nathalie Amzallag; Isabelle Bernard-Pierrot; Xavier Sastre-Garau; Clotilde Théry (PLoS ONE, 2013)
Milk Fat Globule--EGF--factor VIII (MFGE8), also called lactadherin, is a secreted protein, which binds extracellularly to phosphatidylserine and to αvβ3 and αvβ5 integrins. On human and mouse cells expressing these integrins, such as endothelial cells, phagocytes and some tumors, MFGE8/lactadherin has been shown to promote survival, epithelial to mesenchymal transition and phagocytosis. A protumoral function of MFGE8 has consequently been documented for a few types of human cancers, including melanoma, a subtype of breast cancers, and bladder carcinoma. Inhibiting the functions of MFGE8 could thus represent a new type of therapy for human cancers. Here, we show by immunohistochemistry on a collection of human ovarian cancers that MFGE8 is overexpressed in 45% of these tumors, and we confirm that it is specifically overexpressed in the triple-negative subtype of human breast cancers. We have established new in vitro assays to measure the effect of MFGE8 on survival, adhesion and migration of human ovarian and triple-negative breast cancer cell lines. Using these assays, we could identify new MFGE8-specific monoclonal antibodies, which efficiently blocked these three tumor-promoting effects of MFGE8. Our results suggest future use of MFGE8-blocking antibodies as new anti-cancer therapeutics in subgroups of ovarian carcinoma, and triple-negative breast carcinoma patients.